Prawne aspekty ochrony małoletnich przed nikotynizmem: brak - Kilińska-Pękacz, Agnieszka (Studia Prawnoustrojowe, 2019)
Protecting minors from nicotinism involves a ban on the sale of tobacco products to them, as well as prohibitions on their sale in places where they most often stay. Limitations on the advertising of such products are also important here. Their breach results in liability for offenses. This protection covers not only traditional such products, but also electronic cigarettes. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> roniczne. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">